(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Polymer electrolytes are considered an alternative to liquid electrolytes for lithium-ion batteries due to their high thermal stability, flexibility, and wide applications. However, polymer electrolytes have low ionic conductivity at room temperature due to interfacial contact issues and growth of lithium dendrites in electrolytes/electrodes. Polymer gel electrolytes were prepared by a gelation method with different O/Na ratios using PVdF as the polymer host, sodium iodide as the salt, and DMF as the solvent. After synthesis it is characterized by different experimental techniques.